2022
DOI: 10.1507/endocrj.ej21-0490
|View full text |Cite
|
Sign up to set email alerts
|

Urolithin A ameliorates diabetic retinopathy <i>via</i> activation of the Nrf2/HO-1 pathway

Abstract: Diabetic retinopathy (DR) is a progressive microvascular complication of diabetes mellitus and is characterised by excessive inflammation and oxidative stress. Urolithin A (UA), a major metabolite of ellagic acid, exerts anti-inflammatory and antioxidant functions in various human diseases. This study, for the first time, uncovered the role of UA in DR pathogenesis. Streptozotocin-induced diabetic rats were used to determine the effects of UA on blood glucose levels, retinal structures, inflammation, and oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…This conclusion was also supported by Lee et al They pointed out that Uro A prevented DM-associated AD by reducing transglutaminase type 2 (TGM2)-dependent mitochondria-associated ER membrane (MAM) formation and maintaining mitochondrial calcium and ROS homeostasis [35]. Xu et al indicated that Uro A ameliorated diabetic retinopathy by activating the Nrf2/HO-1 pathway to inhibit inflammation and oxidative stress [114]. Zhou et al found that Phyllanthus emblica L. facilitated vascular function in STZ-induced hyperglycemia rats by regulating Akt/β-catenin signaling, mediated by the ETs metabolites [115].…”
Section: Protects Pancreatic β Cellsmentioning
confidence: 74%
“…This conclusion was also supported by Lee et al They pointed out that Uro A prevented DM-associated AD by reducing transglutaminase type 2 (TGM2)-dependent mitochondria-associated ER membrane (MAM) formation and maintaining mitochondrial calcium and ROS homeostasis [35]. Xu et al indicated that Uro A ameliorated diabetic retinopathy by activating the Nrf2/HO-1 pathway to inhibit inflammation and oxidative stress [114]. Zhou et al found that Phyllanthus emblica L. facilitated vascular function in STZ-induced hyperglycemia rats by regulating Akt/β-catenin signaling, mediated by the ETs metabolites [115].…”
Section: Protects Pancreatic β Cellsmentioning
confidence: 74%
“…Urolithin A at a concentration of 10 µM on high glucose-induced human retinal endothelial (HRE) cells counteracted the oxidative stress, increasing SOD activity and GSH levels and reducing MDA, IL-6, IL-1β, and TNF-α levels and gene expression [152]. The Urolithin A and urolithin B modulate oxidative stress and are recognized as emerging antioxidant coumarin derivatives, reducing ROS generation, free radical scavenging, and activating the Nrf2 signaling pathway through Nrf2 nuclear translocation with further upregulation of HO-1, SOD, glutathione-related antioxidant system, and NQO1 [148].…”
Section: Intestinal Anti-inflammatory Gut Microbial Coumarins Targeti...mentioning
confidence: 99%
“…The Urolithin A and urolithin B modulate oxidative stress and are recognized as emerging antioxidant coumarin derivatives, reducing ROS generation, free radical scavenging, and activating the Nrf2 signaling pathway through Nrf2 nuclear translocation with further upregulation of HO-1, SOD, glutathione-related antioxidant system, and NQO1 [148]. The antioxidant properties of urolithin A and urolithin B were related to the control of several diseases such as diabetes, skin aging, sclerosis, kidney and liver toxicity, inflammation, and osteoclastogenesis [152][153][154][155][156][157][158][159].…”
Section: Intestinal Anti-inflammatory Gut Microbial Coumarins Targeti...mentioning
confidence: 99%
“…Intestinal microorganisms metabolize ellagic acid from raspberry to produce urolithin A, which stimulates nuclear NRF2 and HO-1 levels both in vivo and in vitro, activating the NRF2/HO-1 pathway. 59 Ellagic acid/ urolithin has been shown to have good potential in treating ROS-induced neurodegeneration by reducing oxidative stress and preventing inflammation.…”
Section: Food and Function Reviewmentioning
confidence: 99%